Validation of Korean Version of Coma Recovery Scale-Revised (K-CRSR) - Hee Jun Han; Ee Jin Kim; Hae Jin Lee; Sung Bom Pyun; Kyung Lim Joa; Han Young Jung (Annals of Rehabilitation Medicine, 2018)
Objective To determine the validity and reliability of the Korean version of the Coma Recovery Scale-Revised (K-CRSR) for evaluation of patients with a severe brain lesion. Methods With permission from Giacino, the developer of the Coma Recovery Scale Revised (CRSR), the scale was translated into Korean and back-translated into English by a Korean physiatrist highly proficient in English, and then verified by the original developer. Adult patients with a severe brain lesion following traumatic brain injury, stroke, or hypoxic brain injury were examined. To assess the inter-rater reliability, all patients were tested with K-CRSR by two physiatrists individually. To determine intra-rater reliability, the same test was re-administered by the same physiatrists after three days. Results Inter-rater reliability (k=0.929, p<0.01) and intra-rater reliability (k=0.938, p<0.01) were both high for total K-CRSR scores. Inter- and intra-rater agreement rates were very high (94.9% and 97.4%, respectively). The total K-CRSR score was significantly correlated with K-GCS (r=0.894, p<0.01), demonstrating sufficient concurrent validity. Conclusion K-CRSR is a reliable and valid instrument for the assessment of patients with brain injury by trained physiatrists. This scale is useful in differentiating patients in minimally conscious state from those in vegetative state.